EFEKTIVITAS BUAH BELIMBING (Averrhoa carambola) TERHADAP PENURUNAN TEKANAN DARAH PADA PENDERITA HIPERTENSI DI WILAYAH KERJA PUSKESMAS MEDAN SUNGGAL: EFEKTIVITAS BUAH BELIMBING (Averrhoa carambola) TERHADAP PENURUNAN TEKANAN DARAH PADA PENDERITA HIPERTENSI DI WILAYAH KERJA - Sri Wahyuni; Leli Herawati; Nurindah Lestari Ritonga (Fakultas Keperawatan Institut Kesehatan Deli Husada, 2026)
Hypertension is a non-communicable disease often referred to as a “silent killer” because it frequently presents without specific symptoms while increasing the risk of severe complications such as stroke and cardiovascular disease. Hypertension management can be conducted through both pharmacological and non-pharmacological approaches. One potential non-pharmacological intervention is the consumption of star fruit (Averrhoa carambola), which contains potassium, vitamin C, and dietary fiber that may contribute to blood pressure reduction. This study aimed to determine the effectiveness of star fruit in reducing blood pressure among patients with hypertension in the working area of Medan Sunggal Public Health Center. This study employed a quasi-experimental design with a one-group pretest–posttest approach. A total of 30 respondents were selected using purposive sampling. The intervention consisted of administering 150 ml of star fruit juice once daily for three consecutive days. Blood pressure measurements were obtained before and after the intervention using a digital sphygmomanometer. Data were analyzed using the Wilcoxon Signed Rank Test. The results demonstrated a reduction in the mean systolic blood pressure from 147 mmHg to 139.33 mmHg and diastolic blood pressure from 93 mmHg to 78 mmHg following the intervention. Statistical analysis using the Wilcoxon Signed Rank Test revealed significant differences in both systolic (p = 0.000) and diastolic blood pressure (p = 0.008), indicating that star fruit juice had a significant effect on lowering blood pressure among hypertensive patients. In conclusion, star fruit juice was found to be effective in reducing blood pressure and may serve as an alternative non-pharmacological therapy for hypertension management.